Municipal Government Finance Problems: A Growing Concern - Paul, Ritwik; Charmkar, Ramsiya (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The soundness of local government finance has taken on top priority, and eyes have been opened to the windfall of inevitable local government bankruptcy. The dilemmas confronting the local government are an increase in expenditures —particularly in public safety, infrastructure costs, and healthcare —and stagnant or decreasing revenue streams. The proliferation of intergovernmental transfers, property taxes, and fees, in combination with greater volatility in the business cycle, has led to fiscal instability among local governments. In addition, the increasing intolerance regarding the accumulation of unfunded pension liabilities and mounting debt obligations intensifies the financial distress. This abstract will highlight the roots of municipal finance problems, their effects on service provision, and some possible means to promote the long-term fiscal health of local governments. It highlights the necessity of better fiscal management, broader revenue streams, and structural reforms to enable local governments to provide for burgeoning urban populations and fiscal health alike.